Conformational states dynamically populated by a kinase determine its function - Xie, Tao; Saleh, Tamjeed; Rossi, Paolo; Kalodimos, Charalampos G (Science (American Association for the Advancement of Science), 2020)
Protein kinases intrinsically sample a number of conformational states with distinct catalytic and binding activities. We used nuclear magnetic resonance spectroscopy to describe in atomic-level detail how Abl kinase interconverts between an active and two discrete inactive structures. Extensive differences in key structural elements between the conformational states give rise to multiple intrinsic regulatory mechanisms. The findings explain how oncogenic mutants can counteract inhibitory mechanisms to constitutively activate the kinase. Energetic dissection revealed the contributions of the activation loop, the Asp-Phe-Gly (DFG) motif, the regulatory spine, and the gatekeeper residue to kinase regulation. Characterization of the transient conformation to which the drug imatinib binds enabled the elucidation of drug-resistance mechanisms. Structural insight into inactive states highlights how they can be leveraged for the design of selective inhibitors.